2009
DOI: 10.1021/es8035779
|View full text |Cite
|
Sign up to set email alerts
|

Temperature Sensitivity Indicates That Chlorination of Organic Matter in Forest Soil Is Primarily Biotic

Abstract: Old assumptions that chloride is inert and that most chlorinated organic matter in soils is anthropogenic have been challenged by findings of naturally formed organochlorines. Such natural chlorination has been recognized for several decades, but there are still very few measurements of chlorination rates or estimates of the quantitative importance of terrestrial chlorine transformations. While much is known about the formation of specific compounds, bulk chlorination remains poorly understood in terms of mech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
63
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(66 citation statements)
references
References 30 publications
3
63
0
Order By: Relevance
“…However, naturally-occurring organic Cl compounds occur in relatively pristine ecosystems such as forest soils [50]. The surface layer might be richest in organic Cl compounds, having the highest OM content, being closest to inputs of Cl − from rain, and being most subject to oxidative reactions that can lead to the production of reactive Cl compounds and chlorination of OM [51]. On the other hand, it has been suggested that organic Cl compounds can form abiotically as a result of Fe(III) reduction [52], a mechanism likely to occur in anoxic layers of these soils.…”
Section: Resultsmentioning
confidence: 99%
“…However, naturally-occurring organic Cl compounds occur in relatively pristine ecosystems such as forest soils [50]. The surface layer might be richest in organic Cl compounds, having the highest OM content, being closest to inputs of Cl − from rain, and being most subject to oxidative reactions that can lead to the production of reactive Cl compounds and chlorination of OM [51]. On the other hand, it has been suggested that organic Cl compounds can form abiotically as a result of Fe(III) reduction [52], a mechanism likely to occur in anoxic layers of these soils.…”
Section: Resultsmentioning
confidence: 99%
“…More than 4,400 natural organohalogens have been identified (6), and the production of these compounds is becoming well understood (1,2,7,8,9). Studies on the degradation of naturally occurring organochlorines, however, are generally lacking.…”
mentioning
confidence: 99%
“…Several recent studies have indicated that, rather than being unreactive, Cl -participates in a complex biogeochemical cycle (Öberg et al 2005a;Öberg et al 2005b;Bastviken et al 2007;Bastviken et al 2009). Chloride can be immobilized in ecosystems by several different processes, including (1) ion exchange (Larsson and Jarvis 1999), (2) adsorption onto iron and aluminum oxides (Nodvin et al 1986), (3) uptake by biota, including vegetation and microbes (Ohrui and Mitchell 1996;Lovett et al 2005;Bastviken et al 2009), and (5) conversion to organic forms of chlorine (Clutterbuck et al 1940;Myneni 2002;Bastviken et al 2007).…”
mentioning
confidence: 99%
“…Chloride can be immobilized in ecosystems by several different processes, including (1) ion exchange (Larsson and Jarvis 1999), (2) adsorption onto iron and aluminum oxides (Nodvin et al 1986), (3) uptake by biota, including vegetation and microbes (Ohrui and Mitchell 1996;Lovett et al 2005;Bastviken et al 2009), and (5) conversion to organic forms of chlorine (Clutterbuck et al 1940;Myneni 2002;Bastviken et al 2007). …”
mentioning
confidence: 99%